Mitochondrial genome SNPs analysis of eight barley genotypes displaying hot spot regions, phylogenetic relationships and heteroplasmy. (2nd January 2021) - Al-Attas, Bashaer E.; Ali, Hani M.; Khan, Thana; Edris, Sherif; Gadalla, Nour O.; Ramadan, Ahmed M.; Bahieldin, Ahmed
Abstract: Organellar genomes are small, circular entities that provide unique advantages as compared to the nuclear genome. The present study was aimed at evaluating the efficiency of utilizing mitochondrial single nucleotide polymorphisms (SNPs) approach in separating barley cultivars. Sequences generated via next-generation sequencing were further utilized to confirm the incidence of heteroplasmy in barley mitochondrial genome. The analysis involved seven cultivated barley ( Hordeum vulgare subsp. vulgare ) (VG) and one wild ( H. vulgare subsp. spontaneum ) (SP) genotypes. A total of 73 million paired-end reads per mitochondrial genomes across the eight barley genotypes were generated using Illumina HiSeq 2000 platform. Sequences of each genotype were separately aligned to the published barley mitochondrial reference genome, thus SNPs were detected. The overall results indicated the efficiency of using mitochondrial SNPs as a molecular marker in distinguishing among barley genotypes. Unique SNPs were determined in six out of the eight genotypes, where Giza131 and Giza129 had no specific mitochondrial SNPs, while Giza130 showed the largest number of unique mitochondrial SNPs. The phylogenetic tree indicated the close relationship between Giza129 and Giza130. Interestingly, SP was not clearly discriminated among genotypes.